2020
DOI: 10.1007/s40195-020-01035-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Finish Rolling Temperature on Microstructure and Mechanical Properties of a 19Cr1.5Mo0.5 W Ferritic Stainless Steel

Abstract: A 444-type heat-resistant ferritic stainless steel containing 0.05 wt% Ce (rare earth element) and 2 wt% (Mo + W) was adopted as an experimental material to study the effect of finish rolling temperature on microstructure and texture evolution as well as on mechanical properties and formability. The rolling processes contain hot rolling at two different finish rolling temperatures (860 °C and 770 °C) and annealing, cold rolling and subsequent annealing. It was found that the microstructures after hot rolling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In order to obtain heat-resistant ferritic stainless steel with excellent oxidation resistance and considering the above requirements, some research studies have been conducted on related ferritic stainless steel through alloying. These studies have shown that the addition of the alloying element W enhances the high-temperature fatigue performance through precipitation or solid solution strengthening [3] and significantly increases the high-temperature tensile strength [4]. Furthermore, adding alloying elements such as W can improve the thermal mechanical fatigue performance of medium chromium stainless steel [5].…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain heat-resistant ferritic stainless steel with excellent oxidation resistance and considering the above requirements, some research studies have been conducted on related ferritic stainless steel through alloying. These studies have shown that the addition of the alloying element W enhances the high-temperature fatigue performance through precipitation or solid solution strengthening [3] and significantly increases the high-temperature tensile strength [4]. Furthermore, adding alloying elements such as W can improve the thermal mechanical fatigue performance of medium chromium stainless steel [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of rolling plates, temperature is deemed a vital parameter. The temperature of the rolled piece not only affects the structural and mechanical properties of the plate [1,2], but also impacts the rolling force and the shape control [3,4].…”
Section: Introductionmentioning
confidence: 99%